The Communication Strategy of Youth Mosque Preaching in Organizing Congregational Prayers at the Baiturrahman Grand Mosque in Banda Aceh - Safrina Dewi; Khairul Habibi; Kamaruddin Kamaruddin (SAHAFA: Journal of Islamic Communication, 2026)
The Baiturrahman Grand Mosque in Banda Aceh has a dual function as a center of worship and a religious tourism destination, which poses its own challenges in maintaining the solemnity of congregational prayer. This study aims to examine the communication strategy of the Baiturrahman Grand Mosque Youth (RMRB) in disciplining the congregation during prayer amidst the socio-cultural diversity of local and tourist congregations. The research method uses a descriptive qualitative approach through observation, interviews, and documentation. The results show that RMRB applies a structured communication strategy of da’wah through four main approaches: (1) organizational communication based on the principles of tanzhīm and syūrā, which ensures coordination and effectiveness of task division; (2) da’wah communication bil hal, with examples of polite and friendly non-verbal behavior; (3) persuasive communication, which combines religious arguments and a humanist approach according to the theory of interpersonal communication and Islamic public relations; and (4) adaptive communication, which adapts messages to the cultural diversity of the congregation, including foreign tourists. Supporting factors for success include legitimacy from the Mosque Technical Implementation Unit (UPTD), a clear organizational structure, polite communication skills, and members’ commitment to prioritizing the interests of the congregation. Thus, RMRB’s da’wah communication strategy is not merely technical but also represents contemporary da’wah that is humanistic, dialogical, and relevant to the challenges of modern mosque management. Keywords: da’wah communication; mosque youth; Islamic organizational management; prayer, Baiturrahman Grand Mosque